Identification and characterization of ORF19.1725, a novel gene contributing to the white cell pheromone response and virulence-associated functions in Candida albicans. Issue 1 (31st December 2018) - Deng, Fu-Sheng; Lin, Ching-Hsuan
ABSTRACT: An epigenetic transition between white cells and opaque cells influences several properties of Candida albicans biology, including cellular morphology, biofilm formation, virulence, and sexual mating. In particular, these two cell types exhibit marked differences in their ability to undergo sex. A previous study identified the transcriptional regulator of pheromone response in both the white and opaque states as Cph1 because deletion of this gene abolished both pheromone-induced cell adhesion in white cells and sexual mating in opaque cells. To further explore how these cell types exhibit distinct biological outputs upon pheromone stimulation, we selected five Cph1-regulated genes with significant expression during the pheromone response in the white state but not the opaque state. These phase-specific pheromone-induced genes are ORF19.1539, ORF19.1725, ORF19.2430, ORF19.2691 and ORF19.5557 . Deletion of each gene revealed that orf19.1539Δ, orf19.1725Δ, orf19.2430Δ and orf19.5557Δ showed significant decreases in pheromone-stimulated cell adhesion in the white state but retained normal mating competency in the opaque state, indicating that a particular role in white cell pheromone response is mediated by these four genes. Interestingly, the defects of orf19.1725Δ in pheromone-stimulated cell adhesion also abolished conventional biofilms and hyphal growth. Zebrafish egg infection assays further demonstrated that ORF19.1725 is involved in cell adhesion, penetration and virulence. Overall, four Cph1-regulated downstream targets were identified in the regulation of white cell pheromone response. We also clarified the roles of C. albicans ORF19.1725 in cell adhesion, hyphal growth, biofilm formation and virulence.